Effects of rare earth elements on growth and metabolism of medicinal plants - Chunhong Zhang; Qianquan Li; Muxin Zhang; Na Zhang; Minhui Li (Elsevier, 2013)
The rare earth elements (REEs) are a set of 17 chemical elements. They include the lanthanide series from lanthanum (La) to lutetium (Lu), scandium (Sc), and yttrium (Y) in the periodic table. Although REEs are used widely in industry and agriculture in China for a long time, there has been increasing interest in application of REEs to medicinal plants in recent years. In this paper, we summarize researches in the past few decades regarding the effects of REEs on the germination of seeds, the growth of roots, total biomass, and the production of its secondary metabolites, as well as their effects on the absorption of minerals and metals by medicinal plants. By compilation and analysis of these data, we found that REEs have promoting effects at low concentrations and negative effects at comparatively high concentrations. However, most studies focused only on a few REEs, i.e., La, cerium (Ce), neodymium (Nd) and europium (Eu), and they made main emphasis on their effects on regulation of secondary metabolism in tissue-cultured plants, rather than cultivated medicinal plants. Advanced research should be invested regarding on the effects of REEs on yields of cultivated plants, specifically medicinal plants.